Proteomic analysis of a urinary stone with two layers composed of calcium oxalate monohydrate and uric acid. (2nd December 2018) - Kaneko, Kiyoko; Kabeya, Mizuho; Kondo, Hirokazu; Fukuuchi, Tomoko; Yamaoka, Noriko; Yasuda, Makoto; Yamaguchi, Satoshi
Abstract: We examined the mechanism of urinary stone formation by analyzing the matrix proteins in a urinary stone with two layers composed of different crystals. Micro-area X-ray spectrometry and infrared spectroscopy revealed calcium oxalate monohydrate in the outside and uric acid in the inside. We also examined the interface. After the outside, inside, and interface parts were separated, proteomic analysis identified 48, 7, and 4 matrix proteins, respectively. Urinary stones with two layers are considered to have grown under different conditions. The matrix proteins in each part differed among the crystal components and may reveal the stone-generating process. The proteins in the interface likely function to enlarge the stone via the addition of different crystals.